Development and Characterization of Carbon-Based Adsorbents Derived from Agricultural Wastes and Their Effectiveness in Adsorption of Heavy Metals in Waste Water - L. Natrayan; S. Kaliappan; C. Naga Dheeraj Kumar Reddy; M. Karthick; N.S. Sivakumar; Pravin P Patil; S. Sekar; Subash Thanappan (Bioinorganic Chemistry and Applications)
The current work focuses on peanut shells and agricultural wastes richly in many nations subjected to pyrolysis treatment at various temperatures in the range of 500–800°C to determine the feasible physiochemical characteristics of the biochar. The biochars with the high surface area were employed to adsorb Pb2+ (lead) ions, the heaviest pollutants in the water bodies. The raw material, biochar, and pyrolyzed biochar were characterized by SEM, FTIR, partial and elemental analysis, and BET tests. The adsorption characteristics of the biochar, pre- and postpyrolysis treatment, were studied with the assistance of batch adsorption tests under varying test conditions. Adsorbing conditions were determined by evaluating the effects of adsorbing parameters like initial concentration of the lead in water, pH of the adsorbent, contact time, and mixing speed on the effective adsorption of Pb2+ ions from water. Langmuir, Freundlich, and Themkin isotherm expressions were employed to study the experimental results. The adsorption kinetics study showed that the synthesized biochars were chemically stable enough to adsorb the Pb ions onto the surface.